Relationship between BRAF V600E and KRAS mutations in stool for identifying colorectal cancer: A cross-sectional study. (December 2020) - Warsinggih,; Liliyanto,; Marhamah,; Kusuma, M. Ihwan; Uwuratuw, Julianus Aboyaman; Syarifuddin, Erwin; Faruk, Muhammad
Abstract: Background: With early diagnosis, colorectal cancer (CRC) is a curable disease. As studies in the past 15 years have shown, specific genetic changes occur in the neoplastic transformation of normal colonic epithelium to benign adenoma until becoming adenocarcinoma. Considering that dynamic, we aimed to determine how v-raf murine sarcoma viral oncogene homolog B1 (BRAF) V600E and Kirsten rat sarcoma (KRAS) mutations relate to the location, histopathology, and degree of tumor differentiation in CRC. Methods: With a cross-sectional design involving an observational analytical approach, we determined the relationship of BRAF V600E and KRAS mutations to the location, histopathology, and degree of tumor differentiation in CRC. Result: The sample contained 43 patients with CRC aged 21–80 years, with an average age of 56.0 ± 11.2 years, 46.5% of whom were male and 53.5% female, for a male-to-female ratio of 1.0–1.15. Most tumors were located in the right colon ( n = 18, 41.9%), followed by the rectum ( n = 14, 32.6%) and left colon ( n = 18, 25.6%). Non-mucinous adenocarcinoma was more prevalent than mucinous adenocarcinoma, with 22 (51.2%) and 21 (48.8%) patients, respectively. Nineteen tumors were poorly differentiated (44.2%), 15 were moderately differentiated (34.9%), and nine were well-differentiated (20.9%). BRAF V600E mutations totaled six (14%), whereas non- BRAF V600E mutations totaled 37 (86.0%). BRAF V600E mutations significantly related to tumor location, degree of differentiation, and histopathology ( p < .01). Conclusion: A significant relationship exists between BRAF V600E mutations in the stool of patients with CRC and location, histopathology, and degree of tumor differentiation. Highlights: Colorectal cancer (CRC) is the third-leading cause of cancer-related death worldwide. DNA fragment tests of stool can identify CRC. A significant relationship exists between BRAF V600E mutations in the stool of patients with CRC and location, histopathology, and degree of tumor differentiation.